Determining Monsoon Onset Dates in Makassar Using Rainfall Anomalies and Moisture Source Trajectory Analysis (1991–2020) - Hutauruk, Rheinhart; Hadi, Tri Wahyu; Muharsyah, Robi; Yolanda, Selvy (Jurnal Meteorologi dan Geofisika, 2025)
Makassar exhibits a typical monsoonal rainfall regime, characterized by a strong annual cycle with peak rainfall occurring in January–February. Understanding the onset of the rainy season in this region is crucial for water resource management and disaster preparedness, yet previous studies have generally relied only on rainfall-based criteria with coarse temporal resolution. This study aims to determine the onset date of the rainy season in Makassar by combining local rainfall anomalies with regional-scale moisture-source trajectories. Daily rainfall data for 1991–2020 were analyzed using harmonic reconstruction to identify the climatological peak of the monsoon season, which then guided the moisture trajectory analysis. The results show that most rainy-season onsets occur in November–December, with high interannual variability influenced by large-scale climate drivers such as ENSO. Moisture transport during the peak rainy months is predominantly derived from the Northern Maritime (58.8%) and Tropical Maritime (40.5%) sources, highlighting the essential role of cross-equatorial water-vapor advection. In addition, changes in zonal wind direction at 850 hPa consistently coincide with the onset, providing an independent dynamical indicator of the transition from dry to wet phase. By explicitly linking rainfall anomalies with the timing of dynamical shifts and dominant moisture pathways, this approach reduces ambiguities commonly found in rainfall-only methods and produces onset estimates that align more closely with regional atmospheric dynamics. Compared to previous rainfall-only approaches, this combined local–regional method provides a more representative onset estimate at daily resolution, offering new insight into the mechanisms of monsoon rainfall in coastal areas of eastern Indonesia.